SYNTHESIS AND ANTI-ULCER ACTIVITY OF SOME DIHYDROPYRIMIDINES (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Wide range of biological activities is associated with 1, 4-dihydropyridines/ pyrimidines, individually or in combination. In view of this, synthesis of various 6-methyl-4-substitutedphenyl-2-thioxo-1, 2, 3, 4-tetrahydropyrimidine-5-carboxylic acid ethyl esters and 6-methyl-4-substituted phenyl-2-S-alkyl(benzyl)-1, 4-dihydropyrimidine-5-carboxylic acid ethyl esters were undertaken for synthesizing biologically active molecules with improved activity, lesser toxicity with undesirable side effects in clinical use. All the synthesized compounds have been characterized by using IR, Mass studies, 1H NMR and elemental analysis. Further, some compounds were screened for anti-ulcer activity. Compound 4(r) has shown maximum anti-ulcer activity as compared to control group.